MASYARAKAT MULTIKULTURAL : STUDI TENTANG INTERAKSI SOSIAL ANTARA MASYARAKAT ETNIS BALI DAN ETNIS SASAK DI KOTA AMLAPURA - Wicaksana Herlambang, Ida Bagus; Suka Arjawa, I Gst Pt. Bagus; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
ABSTRAK The writing of this paper is urged by the issue that is related with the multicultural society in Bali and social interaction between the ethnics especially the relation between Bali ethnic and Sasak ethnic society that has occured in such long time. This research aims at: To recognize the factors that cause the social interaction happens; To describe the form of social interaction; To recognize the implication in the social life of society. The kind of data used is qualitative and quantitative, meanwhile the data source is primary and secondary data. The technic of collecting data is observation, deep interview, and library study. The determination of informen is by using base informen and key informen. The collected data is analysed by using the qualitative analysis method. In the analysis of the research it is found that the factors cause social interaction between Bali ethnic and Sasak ethnic society in Amlapura city are imitation, suggestion, identification, sympathy. Meanwhile the form of social interaction is associative and dissociative. The implication of social interaction leads to the forming of jagabaya, empowering simakrama, and other form of gathering. Keyword: multicultural society and social interaction.